HUBUNGAN INTENSITAS BERMAIN GAME ONLINE DENGAN KUALITAS TIDUR PADA REMAJA DI SMA NEGERI 1 MUARA DUA KISAM KABUPATEN OGAN KOMERING OKU SELATAN - Sujiah; Gustop Amatiria; Putri Larantika (MOTORIK Jurnal Ilmu Kesehatan, 2025)
The negative impact of playing online games for too long is one of the factors that can influence lack of quality sleep. Online gaming is a phenomenon that is currently popular in Indonesia, including among teenagers or school children. This type of quantitative research uses an analytical survey research design and a cross-sectional approach. The population in this study were all students at SMA Negeri 1 Muara Dua Kisam, South Ogan Komering Oku Regency, Classes X and XI in 2024, totaling 258 teenagers with a sample size of 77 teenagers. In this research, the sampling technique used was accidental sampling. Based on statistical tests, it is known that the p-value is <0.05, namely 0.000, which means that there is a relationship between the intensity of playing online games and the quality of sleep among teenagers at SMA Negeri 1 Muara Dua Kisam, South Ogan Komering Oku Regency in 2024. The research results also show that the majority of teenagers have a maximum duration of playing online games of 6-8 hours. This length of time can cause online game addiction in teenagers. Playing for too long can affect a teenager's eye health and disrupt sleep quality. Suggestion: It is hoped that the results of this research can be used as health information for respondents regarding the relationship between the intensity of playing online games and the quality of sleep in teenagers, so that it is hoped that respondents can make a good game playing schedule, and if necessary reduce playing online games.